Some Thoughts on Biography and the Historiography of the Twentieth-Century Arab World - Parsons, Laila (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2010)
The number of English-language biographies of Arab subjects is tiny compared to the number of English-language biographies of North American and European subjects. I argue that this discrepancy is due to three main factors: the preponderance of historians of Europe and North America in history departments in the English-speaking world; the limited crossover market for serious biographies of Arab subjects; and difficulties arising from access to, and the style of, the Arabic sources. A fragment from the life-story of Fawzi al-Qawuqji, an early-20th-century Arab nationalist and soldier, is introduced as a way of pointing to the challenges of using Arabic memoirs to craft a biographical narrative in English.